An In Vitro Feasibility Study of the Influence of Configurations and Leaflet Thickness on the Hydrodynamics of Deformed Transcatheter Aortic Valve. Issue 8 (24th February 2017) - Feng, Wentao; Yang, Xianda; Liu, Yang; Fan, Yubo
Abstract: Clinically, the percutaneous transcatheter aortic valve (TAV) has been reported to be deformed in a noncircular configuration after its implant. The deformation is universal and various, and it leads to serious leakage and durability problems. Even in the same deformation, the leaflets made in different tissue thicknesses may cause different hydrodynamic performances. Simulating the left heart cardiac conditions by a pulse duplicator system, the present study investigated the effects of the aortic annulus deformation and the leaflet tissue thickness on the hydrodynamics of the TAV. Three 22 mm self‐expanding TAV samples were fabricated with three different leaflet thicknesses (0.25, 0.4, 0.55 mm). Every sample was successively deformed to be elliptical, triangular, and undersized circular shapes. The hydrodynamics of the TAV were assessed through a quasi‐physiological artery pulsatile flow duplicator system. The transvalvular pressure difference, effective orifice area, and regurgitation flow were determined. High‐speed video recordings were taken to investigate the leaflet kinematics. The results showed that the triangular deformation produced the poorest valve function while the elliptical deformation led to the slightest difference from the nominal. With increasing leaflet thickness, the effect of configuration deformation on the regurgitation increased. The thinner leaflets were better than the thicker ones in adapting to the deformation but had a higher risk of deterioration.